Early resting myocardial computed tomography perfusion for the detection of acute coronary syndrome in patients with coronary artery disease - Pursnani, Amit; Schlett, Christopher L. (Circulation. Cardiovascular imaging, 2015)
Background—Acute rest single-photon emission computed tomography-myocardial perfusion imaging (SPECT-MPI) has high predictive value for acute coronary syndrome (ACS) in emergency department patients. Prior studies have shown excellent agreement between rest/stress computed tomography perfusion (CTP) and SPECT-MPI, but the value of resting CTP (rCTP) in acute chest pain triage remains unclear. We sought to determine the diagnostic accuracy of early rCTP, incremental value beyond obstructive coronary artery disease (CAD; ≥50% stenosis), and compared early rCTP to late stress SPECT-MPI in patients with CAD presenting with suspicion of ACS to the emergency department. Methods and Results—In this prespecified subanalysis of 183 patients (58.1±10.2 years; 33% women), we included patients with any CAD by coronary computed tomography angiography (CCTA) from Rule Out Myocardial Infarction Using Computer-Assisted Tomography I. rCTP was assessed semiquantitatively, blinded to CAD interpretation. Overall, 31 had ACS and 48 had abnormal rCTP. Sensitivity and specificity of rCTP for ACS were 48% (95% confidence interval [CI], 30%-67%) and 78% (95% CI, 71%-85%), respectively. rCTP predicted ACS (adjusted odds ratio, 3.40 [95% CI, 1.37-8.42]; P=0.008) independently of obstructive CAD, and sensitivity for ACS increased from 77% (95% CI, 59%-90%) for obstructive CAD to 90% (95% CI, 74%-98%) with addition of rCTP (P=0.05). In a subgroup undergoing late rest/stress SPECT-MPI (n=81), CCTA/rCTP had noninferior discriminatory value to CCTA/SPECT-MPI (area under the curve, 0.88 versus 0.90; P=0.64) using a noninferiority margin of 10%. Conclusions—Early rCTP provides incremental value beyond obstructive CAD to detect ACS. CCTA/rCTP is noninferior to CCTA/SPECT-MPI to discriminate ACS and presents an attractive alternative to triage patients presenting with acute chest pain. Clinical Trial Registration—URL: http://www.clinicaltrials.gov. Unique identifier: NCT00990262.